Analisis Strategi Pengembangan Objek Wisata Pamah Simelir Kabupaten Langkat - Asih, Dimi Setia; Winata, Edi (SEIKO : Journal of Management & Business, 2024)
Tourism villages integrate natural, social, and cultural tourism typical of rural areas. Telagah Village, in Sei Bingai District, Langkat Regency, North Sumatra, was inaugurated as a tourism village through the Sustainable Tourism Village program in 2021. Pamah Simelir Hamlet has agrotourism potential with destinations such as Lake Karona Sakti and Puncak Adem, but faces challenges of minimal facilities and damaged road access. This study uses a qualitative descriptive method to analyze the development strategy of Pamah Simelir through a SWOT analysis. Data were collected through observation, structured interviews, and documentation. The results show that Pamah Simelir has strengths in natural charm and strategic location, but needs to improve facilities and regulations. The resulting strategy is to utilize strengths and opportunities to overcome weaknesses and threats. Support from the government and local community is very important for the success of this tourism development. This research contributes to the planning and management of Pamah Simelir, which is expected to improve the community's economy and preserve local culture.